Language Teachers and Crowdsourcing - Arhar Holdt, Špela; Zanasi, Lorenzo; Weber, Tassja; Volodina, Elena; Rodosthenous, Christos; Ordulj, Antonia; Miloshevska, Lina; Lazić Konjik, Ivana; Koeva, Svetla; Kasperavičienė, Ramunė; Hatipoglu, Ciler; Fort, Karën; et al. (Rasprave Instituta za hrvatski jezik i jezikoslovlje)
The paper presents a cross-European survey on teachers and crowdsourcing. The survey examines how familiar language teachers are with the concept of crowdsourcing and addresses their attitude towards including crowdsourcing into language teaching activities. The survey was administrated via an online questionnaire and collected volunteers’ data on: (a) teachers’ experience with organizing crowdsourcing activities for students/pupils, (b) the development of crowdsourced resources and materials as well as (c) teachers’ motivation for participating in or employing crowdsourcing activities. The questionnaire was disseminated in over 30 European countries. The final sample comprises 1129 language teachers aged 20 to 65, mostly working at institutions of tertiary education. The data indicates that many participants are not familiar with the concept of crowdsourcing resulting in a low rate of crowdsourcing activities in the classroom. However, a high percentage of responding teachers is potentially willing to crowdsource teaching materials for the language(s) they teach. They are particularly willing to collaborate with other teachers in the creation of interactive digital learning materials, and to select, edit, and share language examples for exercises or tests. Since the inclusion of crowdsourcing activities in language teaching is still in its initial stage, steps for further research are highlighted.
Keywords: Linguistics and Language; Language and Linguistics

Präpositionen und Deutsch als Fremdsprache: Quantitative Fallstudien im Lernerkorpus MERLIN - Weber, Tassja
Die Dissertation beschäftigt sich mit dem Gebrauch von Präpositionen (z. B. an, für) und Präpositionalphrasen (z. B. an der Wand, für dich) durch Lernende des Deutschen als Fremdsprache (DaF). Es wird untersucht, welche ausgewählten Variablen den Gebrauch dieser Strukturen beeinflussen. Der Schwerpunkt liegt dabei auf Gebrauchsschwierigkeiten. Auf Basis lernersprachlicher Daten im digitalen, frei verfügbaren Lernerkorpus MERLIN (merlin-platform.eu) und unter Berücksichtigung grundlegender Annahmen aktueller Spracherwerbstheorien werden quantitativ ausgerichtete Fallstudien zu folgenden Einflussvariablen durchgeführt: Die Erstsprache der Lernenden, die Sprachkompetenz, die syntaktische Funktion der PP und der semantische Gehalt der Präposition. Die Arbeit bettet sich ein in die Lernerkorpusforschung an der Schnittstelle zur Zweit- und Fremdspracherwerbsforschung. Die Ergebnisse zeigen insgesamt für alle Einflussvariablen einen Effekt und bestätigen damit den Einfluss intralingualer sowie interlingualer Merkmale im Sprachgebrauch von Lernenden. Dabei wird deutlich, dass die Gebrauchsschwierigkeiten nicht quantitativer (Korrektheit), sondern eher qualitativer Natur (Fehlertypen) sind. Die Dissertation liefert empirisch fundierte Erkenntnisse zu Schwierigkeiten im Gebrauch von Präpositionen und PP durch DaF-Lernende, für die bisher systematische, korpusgestützte Untersuchungen fehlten. Die Arbeit zeigt dabei exemplarisch auf, wie Annahmen aus der Spracherwerbsforschung anhand von Lernerkorpusdaten überprüft und mögliche Einflussvariablen im Sprachgebrauch ermittelt werden können. Die Erkenntnisse sind auch für andere Forschungsfelder (u.a. Fremdsprachenunterricht und maschinelle Sprachverarbeitung) relevant.
Keywords: Deutsch als Fremdsprache; Korpuslinguistik; Lernerkorpora; Präpositionen; Präpositionalphrasen; Grammatik; Regressionsanalyse

Noether’s-type theorems on time scales - Anerot, Baptiste; Cresson, Jacky; Hariz Belgacem, Khaled; Pierret, Frederic (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Noether’s-type theorems on time scales - Anerot, Baptiste; Cresson, Jacky; Hariz Belgacem, Khaled; Pierret, Frederic (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas; Iannuzzi, Marcella; Ben, Mauro Del; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; Golze, Dorothea; Wilhelm, Jan; et al. (The Journal of Chemical Physics)
CP2K is an open source electronic structure and molecular dynamics software package to perform atomistic simulations of solid-state, liquid, molecular, and biological systems. It is especially aimed at massively parallel and linear-scaling electronic structure methods and state-of-theart ab initio molecular dynamics simulations. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern high-performance computing systems. This review revisits the main capabilities of CP2K to perform efficient and accurate electronic structure simulations. The emphasis is put on density functional theory and multiple post–Hartree–Fock methods using the Gaussian and plane wave approach and its augmented all-electron extension.

A Submatrix-Based Method for Approximate Matrix Function Evaluation in the Quantum Chemistry Code CP2K - Lass, Michael; Schade, Robert; Kühne, Thomas; Plessl, Christian (Proc. International Conference for High Performance Computing, Networking, Storage and Analysis (SC))
Electronic structure calculations based on density-functional theory (DFT) represent a significant part of today's HPC workloads and pose high demands on high-performance computing resources. To perform these quantum-mechanical DFT calculations on complex large-scale systems, so-called linear scaling methods instead of conventional cubic scaling methods are required. In this work, we take up the idea of the submatrix method and apply it to the DFT computations in the software package CP2K. For that purpose, we transform the underlying numeric operations on distributed, large, sparse matrices into computations on local, much smaller and nearly dense matrices. This allows us to exploit the full floating-point performance of modern CPUs and to make use of dedicated accelerator hardware, where performance has been limited by memory bandwidth before. We demonstrate both functionality and performance of our implementation and show how it can be accelerated with GPUs and FPGAs.

Janus-type dual emission of a Cyclometalated Iron(III) complex - Bauer, Matthias; Steube, Jakob; Päpcke, Ayla; Bokareva, Olga; Reuter, Thomas; Demeshko, Serhiy; Schoch, Roland; Hohloch, Stephan; Meyer, Franc; Heinze, Katja; Kühn, Oliver; Lochbrunner, Stefan
Photoactive compounds are essential for photocatalytic and luminescent applications, such as photoredox catalysis or light emitting diodes. However, the substitution of noble metals, which are almost exclusively used, by base metals remains a major challenge on the way to a more sustainable world.1 Iron is a dream candidate for this ambitious aim.2 But compared to noble metal complexes that show long-lived metal-to-ligand charge-transfer (MLCT) states, realization of emissive and photoactive iron complexes is demanding, due to the fast deactivation of charge transfer states into non-emissive inactive states. No MLCT emission has been observed for monometallic iron complexes before. Consequently, dual emission could also not yet be realized with iron complexes, as it is a very rare property even of noble metal compounds. Here we report the Fe III complex [Fe(ImP) 2 ][PF 6 ] (HImP = 1,1’-(1,3-phenylene)bis(3-methyl-1-imidazol-2-ylidene)), showing Janus-type dual emission by combining LMCT (ligand-to-metal charge transfer) with MLCT luminescence. The respective excited states are characterized by a record lifetime of τ MLCT = 4.2 ns, and a moderate τ LMCT = 0.2 ns. Only two emissive Fe III compounds are known so far and they show LMCT luminescence only.3,4 The unique properties of the presented complex are caused by the specific ligand design combining four N-heterocyclic carbenes with two cyclometalating groups, using the σ-donor strength of six carbon atoms and the acceptor capabilities of the central phenyl rings. Spectroscopically, doublet manifolds could be identified in the deactivation process, while (TD)DFT analysis revealed the presence of quartets as well. With three key advancements of realizing the first iron complex showing dual luminescence, a MLCT luminescence and a world record MLCT lifetime, the results constitute a basis for future application of iron complexes as white light emitters and new photocatalytic reactions making use of the Janus-type properties of the developed complex.

Benchmarking the Lifecycle of Knowledge Graphs - Röder, Michael; Sherif, Mohamed; Saleem, Muhammad; Conrads, Felix; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs for eXplainable Artificial Intelligence: Foundations, Applications and Challenges)
Keywords: dice group_aksw roeder sherif saleem fconrads ngonga

Applying edge-counting semantic similarities to Link Discovery: Scalability and Accuracy - Georgala, Kleanthi; Röder, Michael; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
With the growth in number and variety of RDF datasets comes an in- creasing need for both scalable and accurate solutions to support link discovery at instance level within and across these datasets. In contrast to ontology matching, most linking frameworks rely solely on string similarities to this end. The limited use of semantic similarities when linking instances is partly due to the current literature stating that they (1) do not improve the F-measure of instance linking approaches and (2) are impractical to use because they lack time efficiency. We revisit the combination of string and semantic similarities for linking instances. Contrary to the literature, our results suggest that this combination can improve the F-measure achieved by instance linking systems when the combination of the measures is performed by a machine learning approach. To achieve this in- sight, we had to address the scalability of semantic similarities. We hence present a framework for the rapid computation of semantic similarities based on edge counting. This runtime improvement allowed us to run an evaluation of 5 bench- mark datasets. Our results suggest that combining string and semantic similarities can improve the F-measure by up to 6% absolute.
Keywords: 2020 dice simba sherif hecate ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal roeder georgala

LIGON – Link Discovery with Noisy Oracles - Sherif, Mohamed; Dreßler}, Kevin; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
Link discovery plays a key role in the integration and use of data across RDF knowledge graphs. Active learning approaches are a common family of solutions to address the problem of learning how to compute links from users. So far, only active learning from perfect oracles has been considered in the literature. However, real oracles are often far from perfect (e.g., in crowdsourcing). We hence study the problem of learning how to compute links across knowledge graphs from noisy oracles, i.e., oracles that are not guaranteed to return correct classification results. We present a novel approach for link discovery based on a probabilistic model, with which we estimate the joint odds of the oracles’ guesses. We combine this approach with an iterative learning approach based on refinements. The resulting method, Ligon, is evaluated on 10 benchmark datasets. Our results suggest that Ligon configured with 10 iterations and 10 training examples per iteration achieves more than 95% of the F-measure achieved by state-of-the-art algorithms trained with a perfect oracle. Moreover, Ligon outperforms batch learning approaches devised to be trained with small amounts of training data by more than 40% F-measure on average.
Keywords: 2020 dice simba sherif ligon ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal kevin

Tentris – A Tensor-Based Triple Store - Bigerl, Alexander; Conrads, Felix; Behning, Charlotte; Sherif, Mohamed; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web -- ISWC 2020)
Keywords: sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:simba sys:relevantFor:limbo sys:relevantFor:raki daikiri speaker tentris knowgraphs bigerl fconrads saleem sherif ngonga group_aksw dice

ProBERT: Product Data Classification with Fine-tuning BERT Model - Zahera, Hamada Mohamed Abdelsamee; Sherif, Mohamed (Proceedings of Mining the Web of HTML-embedded Product Data Workshop (MWPD2020))
Keywords: 2020 dice zahera sherif knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal

LIGER – Link Discovery with Partial Recall - Georgala, Kleanthi; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
Modern data-driven frameworks often have to process large amounts of data periodically. Hence, they often operate under time or space constraints. This also holds for Linked Data-driven frameworks when processing RDF data, in particular, when they perform link discovery tasks. In this work, we present a novel approach for link discovery under constraints pertaining to the expected recall of a link discovery task. Given a link specification, the approach aims to find a subsumed link specification that achieves a lower run time than the input specification while abiding by a predefined constraint on the expected recall it has to achieve. Our approach, dubbed LIGER, combines downward refinement oper- ators with monotonicity assumptions to detect such specifications. We evaluate our approach on seven datasets. Our results suggest that the different implemen- tations of LIGER can detect subsumed specifications that abide by expected recall constraints efficiently, thus leading to significantly shorter overall run times than our baseline.
Keywords: 2020 dice simba sherif hecate ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal georgala

„Wir müssen die Sorgen der Menschen ernst nehmen“ – Zur sprachlichen Thematisierung von Sorge und Angst in der Politik - Georgi, Christopher (Diskurs – ethisch)

Prudence and prevention: Empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik
Theoretical papers show that optimal prevention decisions in the sense of selfprotection (i.e., primary prevention) depend not only on the level of (second-order) risk aversion but also on higher-order risk preferences such as prudence (third-order risk aversion). We study empirically whether these theoretical results hold and whether prudent individuals show less preventive (self-protection) effort than non-prudent individuals. We use a unique dataset that combines data on higher-order risk preferences and various measures of observed real-world prevention behavior. We find that prudent individuals indeed invest less in self-protection as measured by influenza vaccination. This result is driven by high risk individuals such as individuals >60 years of age or chronically ill. We do not find a clear empirical relationship between riskpreferences and prevention in the sense of self-insurance (i.e. secondary prevention). Neither risk aversion nor prudence is related to cancer screenings such as mammograms, Pap smears or X-rays of the lung.
Keywords: prudence; risk preferences; prevention; vaccination; screening

Sprachsensible Formulierung von Erhebungsinstrumenten - Schwabl, Franziska; Janssen, Elmar; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

»auch auf gesanglichem Gebiete überaus thätig«. Max Reger und das Lied - Ried, Dennis (Musik in Baden-Württemberg. Jahrbuch 2019/20)

Do product testing programs lead to more favorable online reviews? (ausgezeichnet mit Best Paper Award) - Garnefeld, I.; Krah, T.; Böhm, Eva; Gremler, D. D. (2020 AMA Winter Academic Conference, San Diego, CA)

Manufacturers’ service growth through mergers and acquisitions – An event study - Eggert, A.; Böhm, Eva; Akalan, R.; Gebauer, H. (2020 AMA Winter Academic Conference, San Diego, CA)

Literarisches Wissen vom marxistischen Wissenschaftsbetrieb. Historiographische Ideologiedebatten in Gerti Tetzners „Karen W.“ - Elit, Stefan (Wirkendes Wort)